PERLINDUNGAN FOLKLOR MENURUT UU HAK CIPTA PERKEMBANGANNYA DAN PERBANDINGANNYA DENGAN NEGARA-NEGARA LAIN - Bungana PA, Reh (Yustisia, 2012)
AbstractProtection of folklore is very important. Indonesia set folklore in the Copyright Act of 2002. In the Copyright Act of 2002 provisions on folklore contained in Article 10, but the settings of folklore in the Copyright Act of 2002 was inadequate, so it is still happening some of Indonesian folklore claimed by foreign countries. Internationally, as yet there is uniformity in the protection of folklore. Regulations in the protection of folklore in every country there has been no uniformity as well. There is a set folklore widely in intellectual property law, but some are set specifically in the Copyright Act.